2020
DOI: 10.3389/fcell.2020.00326
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells and Atopic Dermatitis: A Review

Abstract: Mesenchymal stem/stromal cells (MSCs) are stromal-derived non-hematopoietic progenitor cells that reside in and can be expanded from various tissues sources of adult and neonatal origin, such as the bone marrow, umbilical cord, umbilical cord blood, adipose tissue, amniotic fluid, placenta, dental pulp and skin. The discovery of the immunosuppressing action of MSCs on T cells has opened new perspectives for their use as a therapeutic agent for immune-mediated disorders, including allergies. Atopic dermatitis (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 103 publications
0
42
0
2
Order By: Relevance
“…The skin is the largest organ, accounting for 16% of the body weight, protecting the organisms from external physical (e.g., ultraviolet radiation), organic, or biological aggressions [ 185 ]. There are many diseases and processes such as atopic dermatitis [ 186 ]; psoriasis [ 187 ]; or, especially, chronic skin wounds [ 188 ], which need new therapeutic approaches, constituting MSC as a possibility.…”
Section: New Horizons For Clinical Applications Of Mscmentioning
confidence: 99%
“…The skin is the largest organ, accounting for 16% of the body weight, protecting the organisms from external physical (e.g., ultraviolet radiation), organic, or biological aggressions [ 185 ]. There are many diseases and processes such as atopic dermatitis [ 186 ]; psoriasis [ 187 ]; or, especially, chronic skin wounds [ 188 ], which need new therapeutic approaches, constituting MSC as a possibility.…”
Section: New Horizons For Clinical Applications Of Mscmentioning
confidence: 99%
“…Acute and chronic AD: AD can be differentiated as acute or chronic based on the presiding immune response. The acute phase of AD is dominated by Th2 cytokines such as IL-4, IL-5, IL-22, IL-13, and IL-33, while the immunological mechanism in chronic AD mostly involves Th1/Th0 responses [25]. Studies have revealed that the first 28 h postallergen exposure results in an immune response predominated by Th2 and Th22 cells, while in long-lasting AD, Th1 cells become authoritative [26].…”
Section: Atopic Dermatitis Phenotypesmentioning
confidence: 99%
“…However, the laboratory values did not show a significant difference at the end of treatment. Three more clinical trials are ongoing in Phase 1, Phase 2 and Phase 1/Phase II [ 158 ].…”
Section: Mesenchymal Stem/stromal Cell Therapy (Msct) In Ad and Cumentioning
confidence: 99%